1999
DOI: 10.1117/12.366296
|View full text |Cite
|
Sign up to set email alerts
|

<title>Multispectral Thermal Imager mission overview</title>

Abstract: The Multispectral Thermal Imager (MTI) is a research and development project sponsored by the Department of Energy and executed by Sandia and Los Alamos National Laboratories and the Savannah River Technology Center. Other participants include the U. S. Air Force, universities, and many industrial partners. The MTI mission is to demonstrate the efficacy of highly accurate multispectral imaging for passive characterization of industrial facilities and related environmental impacts from space. MTI provides simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The data used in this study were acquired by the MTI [ Szymanski and Weber , 2005; Weber et al , 1999; Kay et al , 1999; Weber , 2000], a Department of Energy (DOE) research satellite. MTI is a multispectral push broom imager with 15 bands from the visible to the thermal infrared (see Figure 3).…”
Section: Mti Satellitementioning
confidence: 99%
“…The data used in this study were acquired by the MTI [ Szymanski and Weber , 2005; Weber et al , 1999; Kay et al , 1999; Weber , 2000], a Department of Energy (DOE) research satellite. MTI is a multispectral push broom imager with 15 bands from the visible to the thermal infrared (see Figure 3).…”
Section: Mti Satellitementioning
confidence: 99%
“…The studies reported in this paper use a reduced number of relatively wide spectral bands. This reduction in the number of spectral bands was performed to match the bands of a new remote sensing satellite called the Multispectral Thermal imager (MTI) [5] tral filter functions to produce simulated MTI data. This 10-band simulated data was also used in Ref.…”
Section: A Data Used In the Experimentsmentioning
confidence: 99%
“…1,2 The images are also being used for other earth science applications. Calibration and testing of the MTI imager has frequently made use of instrumented ground sites such as DOE's ARM (Atmospheric Radiation Monitoring) locations in the Southern Great Plains and the Tropical Western Pacific (TWP).…”
Section: Introductionmentioning
confidence: 99%